A snap on quality management in Zimbabwe: a perspectives review - Vitalis Basera; Judy Mwenje; Samson Ruturi (Annals of Management and Organization Research, 2019)
Purpose: The main objective of this article was to provide evidence concerning the level of Quality Management (QM) in Zimbabwe. Submitted evidence regarding QM in Zimbabwe will help organizations that want to implement QM systems. The results can guide government agents in making informed decisions towards QM systems implementation since very few organizations are officially quality certified. Research Methodology: The survey followed online search query on quality management in zimbabwe from journal articles, proceedings and institutional repository. 51 publications were selected and excel file was used to capture data and analyse. Results: The results expose that there was high interest in QM in 2014, 2015 and 2016. The results showed industries lack of capacity and resources, lack of skills and expertise, poor communication with stakeholders, poor raw materials, changing customer preferences, lack of top management commitment and costs of QM systems as key barriers to QM implementation. Limitations: The study limitation was survey of few studies retrieved through Bindura University online library and open access journal articles, proceedings papers and dissertations/thesis available on institutional repository. Keywords: Zimbabwe, Quality Management (QM), Drivers, Barriers, Benefits